Stakeholders' role in curbing examination malpractice in Nigeria (2013)
This study looked into the roles of some stakeholders ineffectively curbing examination malpratices in Nigeria. Examination as an instrument for decision - making, always create fear and anxiety in the heart of the candidates and other stakeholders, a major reason, why saome candidates and somee other stakeholders engage in examination malpractices. To eradicate this menace are: the government should introduce effective and comprehensive legislation, provide strigent penalties against the use of unfair means in examinations. The government should also ensure that anybody caught in the act of examination malpractices is adequately purnished irrespective of his status or position in the society. The various examining bodies should collaborate to build large examination halls across the nation. They should also collaborate with communities, government, and corporate bodies in building large examination halls. Teachers should ensure that they attend school and classes regularly and endeavour to bring the content of the study to real life situation with use of relevant teaching materials. Parents should provide all the necessary materials including textbooks that will help improve students' performaces, pay unscheduled visits to their children in school to ascertain whether they are making progress or not. It was equally suggested that parents/guardians should establish a positive parent-child relationship with thier children for the progress or not. It was equally suggested that parents/guardians should establish a positive parent-child relationship with their children for the progress of their wards.